2016
DOI: 10.1016/j.neuroimage.2016.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Sheet Probability Index (SPI): Characterizing the geometrical organization of the white matter with diffusion MRI

Abstract: The question whether our brain pathways adhere to a geometric grid structure has been a popular topic of debate in the diffusion imaging and neuroscience society. Wedeen et al. (2012a b) proposed that the brain’s white matter is organized like parallel sheets of interwoven pathways. Catani et al. (2012) concluded that this grid pattern is most likely an artifact, resulting from methodological biases that cause the tractography pathways to cross in orthogonal angles. To date, ambiguities in the mathematical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 52 publications
(98 reference statements)
3
21
0
Order By: Relevance
“…Previous work has shown that the Lie bracket, a mathematical concept from differential geometry, captures information on the existence of sheet structure (Tax et al, 2015; Tax et al, 2014a; Tax et al, 2016b; Wedeen et al, 2012b; Wedeen et al, 2014). Specifically, the Lie bracket can be computed from two vector fields, and is a vector field itself.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has shown that the Lie bracket, a mathematical concept from differential geometry, captures information on the existence of sheet structure (Tax et al, 2015; Tax et al, 2014a; Tax et al, 2016b; Wedeen et al, 2012b; Wedeen et al, 2014). Specifically, the Lie bracket can be computed from two vector fields, and is a vector field itself.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dMRI peaks are not clustered into distinct vector fields a priori. In previous work we have proposed to compute the Lie bracket by reconstructing an extensive amount of path neighborhoods (Tax et al, 2015; Tax et al, 2014a; Tax et al, 2016b), inspired by the qualitative reconstructions in (Wedeen et al, 2012b). More specifically, by taking small ‘loops’ along the tractography pathways of two vector fields, we could obtain an estimate of the Lie bracket.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations